Santet dan Antropologi Agama - Falikhah, Nur (Alhadharah: Jurnal Ilmu Dakwah, 2012)
Various diseases are natural, but there is also a non natural disease. It is deliberately sent by someone with supernatural powers. This disease is known as witchcraft and sorcery. Witchcraft is part of a black magic and is still believed to exist. The intent and purpose of the using witchcraft is usually for negative purposes, hurt, damage, or destructiom by inserting objects into the body of the victim with the help of magical creature such as genie and devils. Witchcraft is used as a way to weaken opponents. Elements that must be present in it are persons who did it, ritual or ceremony, objects, tools, and the mantra or prayer. Witchcraft which is part of the magic, sorcery and a primitive form of religion still prevail in some communities in Indonesia. This takes place because some people in Indonesia believe in animism